Pineapple Juice for Uterine Fundal Height Reduction in Postpartum Mothers - Mulyadi, Jesica; Andriani, Lusi; Andriani, Lusi; Rachmawati, Rachmawati; Rachmawati, Rachmawati (Journal of Maternal and Child Health, 2021)
Background: Uterine subinvolution occurs because the uterus cannot contract properly, causing bleeding, leading to death. Pineapple fruit is one of the herbal plants that can prevent uterine subinvolution and accelerate uterine involution. This study aimed to determine pineapple's effect on the reduction of uterine fundal height in postpartum mothers in Bengkulu City. Subjects and Method: This was a quasi-experiment. This study was conducted in Bengkulu City, Bengkulu, and using maternal postpartum injected oxytocin in the management stage III with one intervention group, namely the given juice pineapple. The sample used as many as 32 mothers postpartum in Bengkulu were taken by purposive sampling, by predetermined criteria. The dependent variable was uterine fundal height. The independent variables were pineapples juice, age, parity, early mobilization, and early initiation of breastfeeding. Data collection was carried out by the means of the direct interview using a questionnaire and observation sheet. The data were analyzed using independent t-test. Results: The bivariate analysis test results using the independent t-test showed that the group that consumed pineapples experienced a decrease in uterine fundal height for three days more than the control group. Pineapples juice (Mean= 2.55; SD= 1.66), without pineapples juice (Mean= 8.39; SD= 1.48; p <0.001). Age for interventions group, (Mean= 33.19; SD= 7.57) and control group (Mean= 27.56; SD= 8.45; p= 0.057). Parity for interventions group, (Mean= 2.38; SD= 1.45) and control group, (Mean= 2.12; SD= 1.31), p= 0.613. Early mobilization for interventions group, (Mean= 0.84; SD= 0.37) and control group, (Mean= 1.26; SD= 0.58), p= 0.022. Early initiation of breastfeeding for interventions group, (Mean= 16.44; SD= 6.64) and control group, (Mean= 16.38; SD= 5.69), p= 0.978. Conclusion: Pineapple juice and early mobilization affect lowering a uterine fundal height in mothers postpartum three days and can help speed up uterine involution in postpartum mother in Bengkulu City, Bengkulu.